Antihyperglycemic and Glucose Homeostasis Effect of Ethanol and DCM Extract of Gymnema Sylvestre on Type 1 Diabetic Model Rat (Journal of Enam Medical College, 2021)
Bacground: Plants have formed the basis for the treatment of diseases in traditional medicine systems for thousands of years and continue to play a major role in the primary health care of about 80% of the world inhabitants. Gymnema sylvestre is one of the most studied herbs which has been claimed to be active against both type of diabetes mellitus.Objective: The dried powder leaves of Gymnema extracted with ethanol and dichloromethane (DCM) and then its effect were studied in streptozotocin induced type 1 diabetic model rat at different prandial state.Materials and Methods: In the present study both of the extracts (GS EthOH and GS DCM) of Gymnema sylvestre produced a significant antihyperglycemic effect in type 1 diabetic model rats when the extract was given 30 minutes before glucose load. The effectiveness of the extracts in type 1 diabetic rats with residual insulin secretion indicates that the hypoglycemic effect of active plant compound(s) is probably mediated either by improving insulin secretion from the existing β cells or by increasing its sensitivity.Results: The baseline value of fasting serum glucose reflects that the degree of damage of β cells by the toxic effect of streptozotocin was gradual. The findings at one week show some spontaneous recovery in water control group and better recovery in all the treated groups. After two weeks, fasting serum glucose level was improved in all the extract treated groups.Conclusion: The data suggest that Gymnema sylvestre leaf extracts improve the glycemic status in type 1 diabetic model rat.J Enam Med Col 2021; 11(2): 72-77